Survival after Pneumocystis jirovecii pneumonia requiring ventilation: A case report - Gladness Nethathe; Nirav Patel (AOSIS, 2016)
Pneumocystis pneumonia (PCP) in patients with the human immunodeficiency virus (HIV) is associated with a high mortality rate, which increases substantially with the need for mechanical ventilation. Local experience of patients with PCP admitted to the intensive care unit has revealed mortality rates close to 100%. We present a case of a 39-year-old HIV-infected man diagnosed with PCP who was successfully weaned from mechanical ventilation after presenting with respiratory distress and severe hypoxaemia. A short review of the literature will also be presented.